Crawling spot thermal nondestructive testing (NDT) for plaster inspection and comparison with dynamic thermography with extended heating; Thermosense XVII, Orlando, FL, United States, April 17, 1995 - Bison P. Paolo; Braggiotti А. Alberto; Bressan Ch. Chiara; Marinetti S. Sergio; Mazzoldi A. Andrea; Vavilov V. P. Vladimir Platonovich (1995, 1995)
Title screen